2019
DOI: 10.1186/s40729-019-0168-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of simvastatin intervention on the healing of bone, soft tissue, and TMJ cartilage in dentistry: a systematic review and meta-analysis

Abstract: The review aimed at assessing the osteopromotive potential as well as soft tissue and temporomandibular joint (TMJ) cartilage healing properties of simvastatin by summarizing its efficacy on the current dental treatment of periodontal bone and soft tissue defects, and temporomandibular joint (TMJ) arthritis from the available animals and human studies. An electronic search was performed on MEDLINE, Scopus, and Cochrane Central Register of Controlled Trials (CENTRAL) using a combination of keywords. A hand sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 37 publications
(70 reference statements)
1
26
0
Order By: Relevance
“…10 In other words, both BPs and simvastatin can block the mevalonate pathway and have a similar effect on osteoclasts, even though they impact different enzymes. 5,9,10 Long-term use of simvastatin might cause osteonecrosis of the jaw, similar to the present case. Two cases of maxillary MRONJ were reported in healthy and non-smoker patients who undertook high-doses of simvastatin for 20 years.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…10 In other words, both BPs and simvastatin can block the mevalonate pathway and have a similar effect on osteoclasts, even though they impact different enzymes. 5,9,10 Long-term use of simvastatin might cause osteonecrosis of the jaw, similar to the present case. Two cases of maxillary MRONJ were reported in healthy and non-smoker patients who undertook high-doses of simvastatin for 20 years.…”
Section: Discussionsupporting
confidence: 85%
“…[1][2][3][4][5] Simvastatin is a cholesterol-lowering drug with some therapeutic effects on bone angiogenesis. 9 It appears to play a significant role in bone regeneration by directly participating in osteoblast activation as well as osteoclast inhibition. 9 Statins drugs inhibit the mevalonate pathway by inhibiting HMG-CoA reductase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approaches to regenerate bone include specific grafting surgical techniques with autogenous bone, substitutes, barrier membranes, growth factors, stem cell therapy, and, lately, osteopromotive pharmacological compounds. Pharmacological approaches have gained in popularity owing to their convenience and advantageous cost‐effectiveness when applied with other grafting techniques 21 . A number of studies have demonstrated that simvastatin can significantly increase bone formation 7,17 .…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacological approaches have gained popularity owing to their convenience and the advantageous cost-effectiveness when applied with other grafting techniques. [19] A number of studies have demonstrated that simvastatin can significantly increase bone formation. [7,15] In addition to direct effect on osteoblasts and osteoclast, the underlying mechanisms are complexed by statins' pleiotropic effects including anti-inflammation, angiogenesis and antibacterial activity which could also play an important role in bone formation.…”
Section: Discussionmentioning
confidence: 99%